(untitled) (Research, Society and Development, 2021)
The region of Coffee Valley, in the state of Rio de Janeiro, has a large part of the land devoted to agriculture and the municipality of Vassouras, as one of the cities that comprise it, has approximately 62% of the area devoted to this practice. The large volume of animal waste and vegetable straw in these rural regions has potential as a raw material for energy generation and can also contribute to the production of organic fertilizers. Rural residues converted into gases and/or organic fertilizers can be used by local agriculture itself, contributing to sustainable development. This work aimed to evaluate the technical feasibility of biomethane production using rural substrates as raw material. For this analysis, the process simulator (SuperPro Designer®) was used. The simulation considered an anaerobic digester with a capacity of 6 tons and feeding 112.5 kg/d of organic material, with 90 kg of dry manure and 22.5 kg of vegetable straw. Data from enzymatic reactions that occur in the anaerobic digestion process were adjusted in the simulator and corresponded to the steps of hydrolysis, acidogenesis, acetogenesis and methanogenesis. After the simulation performed, the technical feasibility of biogas production was verified, with approximately 90 m3 of biogas being generated per day.